Diabetes mellitus in Myanmar: Socio-cultural challenges and strength - Aye, Than Than; Aung, Moe Wint; Oo, Ei Sandar (Journal of Social Health and Diabetes, 2014)
Myanmar is a country with significant administrative and natural divisions. Access to health-care in few parts is adversely affected by socio-economic as well as infrastructural development. With the prevalence of more than 10%, diabetes needs a special attention including the psycho-social management. Major challenges including public health seeking behavioral issues, presence of traditional medicine, life-style and diet and issues pertaining to religion and environmental was studied in the current study to find out ways for improvement in the overall diabetes care in Myanmar. Although, diabetes project, under the guidance and support by World Health Organization, has been implementing the strategies for prevention, early case detection and proper diabetes care in Myanmar, few areas of concern discussed in the paper needs to be taken into consideration and implemented in the project to have the optimal outcome. Not only stake holders but also health-care personals are responsible for improvement in all aspects of diabetes by modification of health-care system and facilitating the desired changes.
Keywords: Access to health; diabetes prevalence; life-style and diet; socio-cultural challenges; traditional medicine